MORPHOLOGICAL CHANGES IN THE ADRENAL GLAND OF BABIES WHO DIED FROM INTRAUTERINE INFECTION - Jumanov Ziyadulla Eshmamatovich; Djumanova Gulchekhra Eshmamatovna (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study aims to analyze the pathomorphological changes in the adrenal glands of neonates who succumbed to intrauterine infections (HII). It investigates the impact of such infections on the adrenal gland's morphological structure and endocrine function. Methods: The study examines cases of intra-fetal infections caused by microorganisms transmitted during pregnancy. Histopathological analyses of the adrenal glands were performed to identify structural and functional alterations caused by these infections. Results: Findings indicate significant morphological changes in the adrenal glands, including disruptions in glandular architecture and evidence of endocrine dysfunction. These alterations highlight the vulnerability of the adrenal gland to intrauterine infections and the subsequent complications that arise in neonates. Novelty: This research provides unique insights into the relationship between intra-fetal infections and adrenal gland pathologies, emphasizing the critical role of the adrenal gland in neonatal health. The findings contribute to a deeper understanding of the systemic effects of intrauterine infections on fetal development.